Media CCT (Card of Critical Thinking) dalam Pembelajaran Matematika - Dyani Primaningsih (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
One of the thinking skills can be developed through mathematics education is critical thinking. Teacher may take one of the steps to stimulate critical thinking skills by means of CCT (Cards of Critical Thinking) learning media. CCT is a learning media in the form of question cards; containing critical thinking questions like